O fenômeno land grabbing como objeto de estudo: complexidade e diversidade - Teixeira, Priscila Péclat Gonçalves (2018)
The conceptions of land and territory have undergone a reconfiguration of meaning in Contemporary Agrarian Law. Within a new context, the emergence of land grabbing has been observed that, in an international perspective, has preoccupied the society and has taken an interest in studies to attain its knowledge. Its existence is visible in the world, because of globalization and the principle of free movement of capital that is inherent. It occurs in countries of Africa, South America and Asia, but also, in particular, in the countries of the European Union. It is emphasized that its concept is still indeterminate and perhaps justified by the fact that researchers have not clearly achieved their forms of manifestation, causes and consequences, given that it is a recent phenomenon. It is a vertiginous race for acquisition and concentration of land, which have been intensified after a world food crisis and the subprime crisis. A central hypothesis that was sought to prove is the land grabbing is a fundamentally economic phenomenon, characterized by the accentuated accumulation, appropriation and exploitation of land, diverging from the dominant thesis that consists of a neocolonial, ideological and geographical view. A philosophical and historical examination of neocolonialism will be made, as well as a Weberian Analysis, through the relation between the law and the capitalist economy, regarding the restrictions and concessions that the legal system provides to the economic agents practicing land grabbing. Firstly, it was sought to understand it, by analyzing its emergence and its places of occurrence, with the score of its characteristics, and then to reach what is the basis of its manifestation. In a second moment, a reconstruction of the vision of the phenomenon is created, starting from its realization in the European States, through the demonstration of concrete cases, by means of bibliographical research, in which it is pointed out, in this way, the main causes, which are directly related to an economic substrate of financial interests of public or private agents, internal or external to the countries in which they occur.